3x+7-9+x=2x+3-x+4

Simple and best practice solution for 3x+7-9+x=2x+3-x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+7-9+x=2x+3-x+4 equation:


Simplifying
3x + 7 + -9 + x = 2x + 3 + -1x + 4

Reorder the terms:
7 + -9 + 3x + x = 2x + 3 + -1x + 4

Combine like terms: 7 + -9 = -2
-2 + 3x + x = 2x + 3 + -1x + 4

Combine like terms: 3x + x = 4x
-2 + 4x = 2x + 3 + -1x + 4

Reorder the terms:
-2 + 4x = 3 + 4 + 2x + -1x

Combine like terms: 3 + 4 = 7
-2 + 4x = 7 + 2x + -1x

Combine like terms: 2x + -1x = 1x
-2 + 4x = 7 + 1x

Solving
-2 + 4x = 7 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-2 + 4x + -1x = 7 + 1x + -1x

Combine like terms: 4x + -1x = 3x
-2 + 3x = 7 + 1x + -1x

Combine like terms: 1x + -1x = 0
-2 + 3x = 7 + 0
-2 + 3x = 7

Add '2' to each side of the equation.
-2 + 2 + 3x = 7 + 2

Combine like terms: -2 + 2 = 0
0 + 3x = 7 + 2
3x = 7 + 2

Combine like terms: 7 + 2 = 9
3x = 9

Divide each side by '3'.
x = 3

Simplifying
x = 3

See similar equations:

| -21=7/8y | | -6=-3/5w | | X+Y-3Z= | | (x^5)^(9/5) | | 5/2v=15 | | 4(b-3)-6=2(b+5) | | 7-4(x-4)=2*x | | -2x+4.25=-2x-8.75 | | e-2=17 | | .5x+18=4 | | 3x+w= | | 5x-1.25=-2x-1.25+7x | | 7+ln(x)=4 | | 157=2x-113+8x | | x+10=3x-5 | | 8(k+1)-(7k-5)=2 | | 2t+3=4-2t | | -7/3*3/13= | | 7(2n-2)=(8n+4)+5 | | 8=7.5+25 | | C-9=4 | | 16x^2-20+4x=0 | | v=15m/10s | | 4t-4=12 | | 6d^3=9d^3 | | -3(8x-6)=-2(2x+2) | | 3/7=4x/21 | | 5x-15=20x-5 | | 108=1/3x^2-5 | | -4-8x=4x+32 | | 3x+23=5-6x | | 8-(-12)/(-6) |

Equations solver categories